Processamento e caracterização de ligas a base de magnésio para uso como implantes bioabsorvíveis - Asato, Gabriel Hitoshi (2015)
Magnesium alloys have attracted great interest for use in temporary orthopedic implants to replace existing materials, due to the combination of physical, mechanical and corrosive properties. A magnesium based alloy containing zinc and calcium have been proposed and studied due to its biocompatibility and lower corrosion rate than the pure element. Zinc improves the mechanical properties and corrosion resistance, increasing the potential for corrosion. Calcium promotes grain refinement during solidification and increases the strength and toughness with a second phase precipitation. Amorphous materials have greater homogeneity of composition resulting in improved corrosion resistance and mechanical properties due to the nature of its structure. Recent research at DEMa-UFSCar showed that levels close to 5% at. were more likely to the formation of amorphous phase. This work aims to study the influence of calcium content in relation to mechanical and corrosive properties. The processing method is also evaluated, taking as parameters the proximity of the composition with the theoretical values and the oxygen content in the composition of the final alloy. The materials were characterized through scanning electron microscopy techniques (SEM), X-ray diffraction (XRD), differential scanning calorimetry (DSC), chemical analysis by optical emission spectrometer with inductively coupled plasma (ICP-OES) and spectrometer absorption of infrared radiation, conventional compression test and potentiodynamic polarization test. The results show that the increase of calcium content favors both compressive strength and corrosion resistance.